Progress on diagnosis and treatment of multisystem inflammatory syndrome in children - Peng, Zhe; Zhou, Gang (Frontiers in Immunology, 2025)
Since the emergence of COVID-19 in December 2019, the novel SARS-CoV-2 virus has primarily affected adults, with children representing a smaller proportion of cases. However, the escalation of the pandemic has led to a notable increase in pediatric cases of Multisystem Inflammatory Syndrome in Children (MIS-C). The pathogenesis of MIS-C is largely attributed to immune-mediated mechanisms, such as cytokine storms and endothelial damage, following SARS-CoV-2 infection. In this review, we comprehensively describe MIS-C, including its definitions as proposed by the CDC, WHO, and RCPCH, which emphasize persistent fever, excessive inflammatory responses, and multi-organ involvement. Additionally, we summarize current treatment approaches, prioritizing immunotherapy with intravenous immunoglobulin and corticosteroids, along with anticoagulation therapy, and monoclonal antibodies in severe cases.